Az első világháború következményei a Rábától délre - Mohos, Mária (Közép-Európai Közlemények, 2009)
The western districts of Vas and Zala counties fell into the middle of an international argument after the World War I. It was impossible to adjust the country borders to ethnical borders because of the mixing of Hungarian and Slovenian population.The ethnical statistics are very important in the case of establishing the number of minorities. During the national census the asked questions changed a lot in the past one hundered years, though they mainly focused on the “Mother Language” and “Nationalitiy” topics. In Hungary at end of the XX. century the number of minorities increased, but the statistics show us different changes. Is this increase real?